2022
DOI: 10.2215/cjn.03040322
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Patients with Liver Disease

Abstract: AKI is commonly encountered in patients with decompensated cirrhosis, and it is associated with unfavorable outcomes. Among factors specific to cirrhosis, hepatorenal syndrome type 1, also referred to as hepatorenal syndrome-AKI, is the most salient and unique etiology. Patients with cirrhosis are vulnerable to traditional causes of AKI, such as prerenal azotemia, acute tubular injury, and acute interstitial nephritis. In addition, other less common etiologies of AKI specifically related to chronic liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 70 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…The demographic information was composed of age, sex, and three hospitals (Itabashi, Hikarigaoka, and Surugadai; dummy variables). The medical history was composed of hypertension, diabetes, heart failure, anemia, sepsis, chronic kidney disease (stage ≤2), and chronic liver disease, which are known risk factors for AKI (ICD-10 codes are shown in Supplementary Table S1B ) ( Poston and Koyner, 2019 ; Ostermann et al, 2020 ; Yu et al, 2020 ; Cullaro et al, 2022 ). A diagnosis was regarded as “present” if there was a diagnosis before baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The demographic information was composed of age, sex, and three hospitals (Itabashi, Hikarigaoka, and Surugadai; dummy variables). The medical history was composed of hypertension, diabetes, heart failure, anemia, sepsis, chronic kidney disease (stage ≤2), and chronic liver disease, which are known risk factors for AKI (ICD-10 codes are shown in Supplementary Table S1B ) ( Poston and Koyner, 2019 ; Ostermann et al, 2020 ; Yu et al, 2020 ; Cullaro et al, 2022 ). A diagnosis was regarded as “present” if there was a diagnosis before baseline.…”
Section: Methodsmentioning
confidence: 99%
“…PAH is a reported prevalence of 5.0–7.5% of hospitalized patients and in 50–60% of critically ill patients [3]. There are substantial causative factors of AKI, like cardiovascular events [4], older adults [5], mechanical ventilator [6], nephrotoxic agents [7], vasopressors [8], hypertension [9], hypercholesterolemia [10], liver disease [11], hypoalbuminemia [12], sepsis [13], renal ischemia [14], diabetes mellitus [15], obesity [16], anemia [17] and chronic kidney disease [18]. Studies have revealed that the progression of AKI is related to genetic factors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clin Chem Lab Med. 2020;58(11):1819-1827. doi:10.1515/cclm-2019-0292 284. Tzveova R, Naydenova G, Yaneva T, Dimitrov G, Vandeva S, Matrozova Y, Pendicheva-Duhlenska D, Popov I, Beltheva O, Naydenov C, et al Gender-Specific Effect of CYP2C8*3 on the Risk of Essential Hypertension in Bulgarian Patients.…”
mentioning
confidence: 99%
“…Over the past decade, there has been extensive research into the mechanisms of distant organ dysfunction caused by AKI, in which the most studied organ was the lung, followed by the heart, brain, liver, and gut [ 4 , 5 , 6 ]. AKI patients with a complication of liver dysfunction had poor clinical outcomes [ 7 , 8 ]. Several clinical studies reported that AKI patients with hepatic dysfunction had alterations in protein synthesis, inflammatory responses, and abnormal metabolism of lipids, proteins, and drugs [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%